2014
DOI: 10.1534/g3.113.008953
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome DNA Methylation Profile of the Jewel Wasp (Nasonia vitripennis)

Abstract: The epigenetic mark of DNA methylation, the addition of a methyl (CH3) group to a cytosine residue, has been extensively studied in many mammalian genomes and, although it is commonly found at the promoter regions of genes, it is also involved in a number of different biological functions. In other complex animals, such as social insects, DNA methylation has been determined to be involved in caste differentiation and to occur primarily in gene bodies. The role of methylation in nonsocial insects, however, has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 29 publications
3
39
0
Order By: Relevance
“…Given that the N. vitripennis methylome has recently been sequenced (Wang et al 2013;Beeler et al 2014), future research will determine which methylated DNA sequences are involved in sex allocation. As we have recently shown that there is (so far) no detectable differential gene expression associated with facultative sex allocation in Nasonia (N. Cook, U. Trivedi, B. Pannebakker, M. Blaxter, M. Ritchie, E. Tauber, T. Sneddon, and D. Shuker, unpublished manuscript), it would appear that disrupting DNA methylation is not having its effect by changing patterns of gene expression during oviposition, but rather the effect must be upstream, perhaps changing the sex allocation machinery prior to the female actually having to allocate sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the N. vitripennis methylome has recently been sequenced (Wang et al 2013;Beeler et al 2014), future research will determine which methylated DNA sequences are involved in sex allocation. As we have recently shown that there is (so far) no detectable differential gene expression associated with facultative sex allocation in Nasonia (N. Cook, U. Trivedi, B. Pannebakker, M. Blaxter, M. Ritchie, E. Tauber, T. Sneddon, and D. Shuker, unpublished manuscript), it would appear that disrupting DNA methylation is not having its effect by changing patterns of gene expression during oviposition, but rather the effect must be upstream, perhaps changing the sex allocation machinery prior to the female actually having to allocate sex.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has confirmed genome-wide DNA methylation in Nasonia, with approximately 30% of genes having methylated CpG sequences, mostly in exons, with methylation typically associated with increased gene expression (Wang et al 2013; see also Beeler et al 2014). Here we use the demethylating agent 5-aza-2 0 -deoxycytidine (5-aza-dC) to manipulate the genome-wide DNA methylation status of female N. vitripennis.…”
Section: Introductionmentioning
confidence: 91%
“…First, we provide a detailed genomic description of methylation in Nasonia vitripennis, which augments the recently published data sets (Wang et al 2013;Beeler et al 2014). Second, we identify differentially methylated sites in females associated with experience of long or short days.…”
mentioning
confidence: 98%
“…Although NVhsp90A showed a similar pattern of expression and level of expression as NVhsp70 and NVlsdp in Sf9 cells and in somatic and germline transformed D. melanogaster, the expression pattern will require mapping in N. vitripennis during development. NVhsp90A is the only sequence examined that shows DNA methylation in the native condition (Beeler et al, 2014) yet it was as active in the Sf9 cells and in D. melanogaster, which largely lacks DNA methylation. This suggests that the methylation state of this TRE is not an essential feature of its efficacy.…”
Section: Discussionmentioning
confidence: 94%
“…This selection scheme provided sequences that had a high likelihood of containing consensus transcriptional regulatory elements for each gene but was not sufficient to include all potential enhancer or regulatory elements for each gene. From this pool, the 5' upstream sequences were examined with consideration to the state of DNA methylation based on comparisons with the bisulphiteconverted DNA libraries (Beeler et al, 2014). Based on these selection criteria, eight unmethylated genes were selected as potential candidates and an additional five methylated genes were selected (Table 1).…”
Section: Identification Of Transcriptional Regulatory Elementsmentioning
confidence: 99%